Atypical Complete Femoral Fractures Associated with Bisphosphonate Use or Not Associated with Bisphosphonate Use: Is There a Difference?. (20th November 2016) - Kim, Sang-Min; Park, Youn-Soo; Moon, Young-Wan; Kang, Seung-Hoon; Yeo, Ingwon; Oh, Seung-Min; Lim, Seung-Jae
Abstract : The purpose of this study is to compare clinical characteristics and surgical outcome of atypical complete femoral fractures associated with bisphosphonates (BPs) use and those of fractures not associated with BPs use. Seventy-six consecutive patients (81 fractures) who had been operatively treated for a complete atypical femoral fracture were recruited. Of the 81 fractures, 73 occurred after BPs medication of at least 3 years (BP group) while 8 occurred without a history of BP medication (non-BP group). There were no differences in demographic data and fracture- and surgery-associated factors between the two groups. Of 76 patients (81 fractures), 54 (66.7%) fractures showed bony union within 6 months after the index surgery and 23 (28.4%) showed delayed union at a mean of 11.2 months (range, 8–18 months). The remaining 4 fractures were not healed, even 18 months after the index surgery. There was no difference in healing rate between the BP group and the non-BP group. There were strong correlations between the fracture height and the degree of bowing regardless of BPs medication. All fractures except 1 occurred at the diaphyseal region of the femur when not associated with BP medication.